Inhibition of FEN1 Increases Arsenic Trioxide-Induced ROS Accumulation and Cell Death: Novel Therapeutic Potential for Triple Negative Breast Cancer - Xin, Xing; Wen, Ti; Gong, Li-Bao; Deng, Ming-Ming; Hou, Ke-Zuo; Xu, Lu; Shi, Sha; Qu, Xiu-Juan; Liu, Yun-Peng; Che, Xiao-Fang; Teng, Yue-E (Frontiers in Oncology, 2020)
Triple-negative breast cancer (TNBC) is an aggressive subtype of breast cancer, which is very difficult to treat and commonly develops resistance to chemotherapy. The following study investigated whether the inhibition of Flap Endonuclease 1 (FEN1) expression, the key enzyme in the base excision repair (BER) pathway, could improve the anti-tumor effect of arsenic trioxide (ATO), which is a reactive oxygen species (ROS) inducer. Our data showed that ATO could increase the expression of FEN1, and the knockdown of FEN1 could significantly enhance the sensitivity of TNBC cells to ATO both in vitro and in vivo. Further mechanism studies revealed that silencing FEN1 in combination with low doses of ATO might increase intracellular ROS and reduce glutathione (GSH) levels, by reducing the nuclear translocation of nuclear factor erythroid 2-related factor 2 (Nrf2); elevating ROS leaded to apoptosis and p38 and JNK pathway activating. In conclusion, our study suggested the combination of FEN1 knockdown and ATO could induce TNBC cell death by promoting ROS production. FEN1 knockdown can effectively decrease the application concentrations of ATO, thus providing a possibility for the treatment of TNBC with ATO.